Efeito pró-cinético da Mangiferina, isolada de Mangifera indica L., em camundongos - Morais, Talita Cavalcante (2015)
Mangiferin is a glucosylxanthone encountered in several traditionally used medicinal plants that has been shown to exhibit multiple pharmacological effects that include antioxidant, anti-inflammatory and gastroprotective. Mangiferin used in this study was extracted and isolated from the stem bark of Mangifera indica L. (mango), and its prokinetic effect was investigated using experimental models of gastrointestinal motility in mice. Mangiferin significantly accelerated gastrointestinal transit at oral doses of 30 and 100 mg/kg (89% and 93%, respectively), compared with the vehicle control (63%). Tegaserod (1mg/kg, i.p.), a known prokinetic, stimulated gastrointestinal transit (81%). In the second series of experiments, mice were used to study the effect of mangiferin (30 mg/kg, po) on gastrointestinal transit delay caused by morphine, clonidine, capsaicin, verapamil, ondansetron or atropine. While co-administered mangiferin totally reversed the inhibitory effects of morphine, ondansetron and capsaicin on gastrointestinal transit, the transit delays caused by clonidine and verapamil were only partially reversed. Atropine completely blocked the stimulant effect of mangiferin, suggesting the involvement of muscarinic acetylcholine receptor. Also, mangiferin (30 and 100 mg/kg, po) significantly increase gastric emptying in mice. Mangiferin at doses of 100 mg/kg and 300 mg/kg, and tegaserod at 1 mg/kg significantly enhanced the fecal pellets output by 52%, 40%, and 80%, respectively, when compared to fecal output in vehicle treated mice. Tegaserod group elevated water content (59%) relative to the vehicle-treated control (51%). Postoperative ileus (POI) in mice was characterized by decreased gastrointestinal transit accompanied by an intestinal inflammatory response. POI caused a significant decrease (46,46 ± 4,56%) of gastrointestinal transit when compared to sham control (75,09 ± 1,88%). The oral treatment with mangiferin (30 and 100 mg/kg) accelerated gastrointestinal transit, reduced myeloperoxidase activity, reduced nitrate/nitrite and inflammatory mediators (TNF-α, IL-1β, IL-6, MCP-1) levels in mice compared to respective vehicle control. Treatment with mangiferin reduced the inflammation and protected the ileus from histological damage induced by POI, and reduced the NF-κB and iNOS immunoreactivity in the ileum. This study indicate the prokinetic action of mangiferin and suggests that could be an alternative to available prokinetic drugs for the treatment of gastrointestinal disturbances such as constipation, dyspepsia and postoperative ileus.